2013
DOI: 10.1002/ijc.28196
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for extrahepatic cholangiocarcinoma: ABO blood group, hepatitis B virus and their synergism

Abstract: Little is known about the role of association between ABO blood group and development of extrahepatic cholangiocarcinoma (ECC) through effects on hepatitis B viral (HBV) infection. Our aim was to address this question using a matched case-control study in Southern China.We prospectively analyzed 239 ECC patients, and 478 age-and sex-matched controls in Sun Yat-sen Memorial Hospital of Sun Yat-sen University from 1999 to 2011. Information on ABO blood group, HBV infection and other clinicopathologic factors was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
1
24
1
Order By: Relevance
“…Among the 39 studies, 26 studies were for ICC, including 13 studies [1114, 16, 17, 19, 22, 23, 25, 26, 29, 31] for estimating the incidence rates of ICC, 11 studies [32, 3436, 3942, 44, 45, 47] for unadjusted OR analysis, and 7 studies [32, 35, 36, 39, 41, 42, 44] for adjusted OR analysis (Tables 3 and 4). Nine studies were for ECC, including 3 studies [11, 15, 20] for estimating the incidence rates of ECC, 5 studies [32, 35, 40, 43, 47] for unadjusted OR analysis, and 1 study [35] for adjusted OR analysis (Tables 4 and 5). The main features of included studies were shown in Tables 1 –5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 39 studies, 26 studies were for ICC, including 13 studies [1114, 16, 17, 19, 22, 23, 25, 26, 29, 31] for estimating the incidence rates of ICC, 11 studies [32, 3436, 3942, 44, 45, 47] for unadjusted OR analysis, and 7 studies [32, 35, 36, 39, 41, 42, 44] for adjusted OR analysis (Tables 3 and 4). Nine studies were for ECC, including 3 studies [11, 15, 20] for estimating the incidence rates of ECC, 5 studies [32, 35, 40, 43, 47] for unadjusted OR analysis, and 1 study [35] for adjusted OR analysis (Tables 4 and 5). The main features of included studies were shown in Tables 1 –5.…”
Section: Resultsmentioning
confidence: 99%
“…For pooled analysis of unadjusted OR of ECC with HBV infection, 6 studies with 14 517 participants including controls were analyzed [15, 32, 35, 40, 43, 47]. The meta-analysis in a random-effects model ( P < 0.001, I 2 = 88.6%) found no statistically significant increased risk of ECC incidence with HBV infection (OR = 1.407, 95% CI 0.925–2.141, P = 0.110, Figure 4(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Hazendonk et al, (30) in their study evaluating the extent and predictors of underdosing and overdosing in perioperative hemophilia A patients, found that blood O patients had a higher risk of perioperative bleeding complications compared to those with blood group non-O. A synergism between blood group A and HBV infection in the development of extrahepatic cholangiocarcinoma has been suggested (31). In their case-control study including 1.538 patients with newly diagnosed HCC, Shim et al (6) from Korea have concluded that blood group A and genotype AA showed the highest risk of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, risk sharing between each primary cancer site and anatomically adjacent organs is also useful regarding the potential mechanism. An association between blood group A, HBV infection, and extrahepatic cholangiocarcinoma (ECC) risk was reported, with synergism between blood group A and HBV infection in the development of ECC (Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%